Applications of assistive technology in skills development for people with Autism Spectrum Disorder: a systematic review (Research, Society and Development, 2021)
The purpose of this systematic review was to present, through a critical approach, interpretation and evaluation, the current assistive technology research directions, and the range, capabilities and efficiency of mobile devices and their respective software applications and the virtual reality and augmented reality environments used for people with autism. The aim was to identify the assistive technology practices applied for the development of communication, social and vocational-employment skills for people with autism, and to evaluate their acceptability and effectiveness. Search in electronic databases resulted in a final selection of 63 studies that met the inclusion criteria of the review, covering a total of 406 participants with autism. Analysis of the data from the studies provided largely positive results.